The Influence of Work-Life Balance, Job Satisfaction, and Transformational Leadership Style on Turnover Intention in Generation Y in Sidoarjo - Amanda Dhyasputri (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This study aims to examine whether or not there is an influence between work-life balance, job satisfaction, and transformational leadership style on turnover intention in generation Y in Sidoarjo, and to examine the most influential variables among the three. This research is a type of quantitative research with a questionnaire research tool distributed to as many as 441 respondents. The test method used is multiple linear regression. The results of this study indicate that: (1) Work-life balance, job satisfaction, and transformational leadership style have been shown to influence turnover intention, either partially or simultaneously. (2) Job satisfaction has a positive effect on turnover intention. (3) Transformational leadership style is the most influential among the three independent variables.